The Effects of Controlling Gas Escape and Bottom Current Activity on the Evolution of Pockmarks in the Northwest of the Xisha Uplift, South China Sea - Xuelin Li; Xudong Guo; Fei Tian; Xiaochen Fang (Journal of Marine Science and Engineering)
Submarine pockmarks are typical indicators of submarine gas escape activity. The deep strata of the Xisha Uplift are rich in biogenic and thermogenic gas, accompanied by strong bottom current activity. Investigating the effects of controlling submarine gas escape and bottom current activity on the formation and development of pockmarks in the Xisha Uplift is significant for understanding the evolution of submarine topography and geomorphology. This study utilized high-resolution multibeam data to identify 261 submarine pockmarks in the northwest of the Xisha Uplift. These pockmarks were categorized based on their morphology into circular, elliptical, elongated, crescent-shaped, and irregular types. The diameters of pockmarks in the study area range from 0.21 to 4.96 km, with maximum depths reaching 30.88 m. Using high-resolution multi-channel seismic data, we conducted a detailed analysis of the subsurface strata characteristics of the pockmarks, identifying chaotic weak reflections, bright spots, and high-angle reflectors. We believe that deep gas in the northwest of the Xisha Uplift escapes to the seafloor through migration pathways, such as faults, fractures, and gas chimneys, resulting in the formation of submarine pockmarks. Bottom current activity has a significant impact on already-formed pockmarks. Crescent-shaped and elongated pockmarks in the Xisha Uplift are largely the result of bottom current modifications of pre-existing pockmarks.